Seed Characterization and Evaluation of Pre-Germinative Barriers in the Genus Alstroemeria (Alstroemeriaceae) - Mitsi, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The genus Alstroemeria originates from South America, and Chile is one of the countries showing the highest number of taxa (49), of which 40 are endemic. However, anthropogenic and environmental factors are affecting the survival of these species; therefore, the conservation of their genetic variability is of great importance, and can be achieved through seed propagation. Seeds of this genus normally show dormancy, which prevents their germination under favorable conditions. The objective of this work was to understand the pre-germinative barriers to develop a seed propagation protocol for native alstroemerias and to determine the best method to break their dormancy. Seeds from 10 Alstroemeria species native to Chile were collected from the Coquimbo Region to Maule Region, and 5 pre-germination treatments combining scarification and stratification methods were evaluated. Moreover, a morphological and biochemical evaluation of the seeds was performed. The results showed a positive and significant effect on the percentage of emergence using seed soaking in water and cold stratification at 13 °C, obtaining the best results in A. pelegrina and A. angustifolia subsp. angustifolia (98.33% and 91.67%, respectively) after 30 days. The morphological characterization of seeds showed a wide range of size (diameter), from 2.18 mm (A. pulchra subsp. pulchra) up to 3.43 mm (A. pelegrina), and different shapes (pseudospherical and angular) and textures (rough and smooth). The highest phenol and tannin concentrations were observed in A. hookeri subsp. maculata with values of 4.71 and 30.95 mg g−1 of seeds, respectively. A bigger size of the seed and a higher concentration of phenols could be related to a higher % of emergence of alstroemeria seeds. © 2023 by the authors.